The Radical Origins of the Deindustrialization Thesis: From Dependency to Capital Flight and Community Abandonment - High, Steven (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2023)
Deindustrialization became a pressing political issue and an object of research almost simultaneously in North America. This article inquires into the intellectual origins and radical roots of the deindustrialization thesis in Canada and the United States. Though the two countries share much in common, their distinctive formulations of the deindustrial problem in the 1970s and 1980s reflected key economic and political differences between them. Radical political economists in Canada and the United States turned to dependency theory and capital flight, respectively, in their theorization of deindustrialization. Barry Bluestone and Bennett Harrison’s 1982 book, The Deindustrialization of America, in particular, is a founding text for the burgeoning field of deindustrialization studies. We can learn much from re-engaging with this early scholarship. In doing so, however, we need to bridge the continuing analytical divide between micro-level labour histories of working-class communities and macro-level studies of political economy and the international division of labour.